Research hotspots and trends of transcranial magnetic stimulation in Parkinson’s disease: a bibliometric analysis - Wei, Yi-xin; Tu, Liang-dan; He, Lin; Qiu, Yi-tong; Su, Wei; Zhang, Li; Ma, Run-ting; Gao, Qiang (Frontiers in Neuroscience, 2023)
Background: Transcranial magnetic stimulation (TMS), as a non-invasive neuromodulation technique, has been widely used in the treatment of Parkinson's disease (PD). The increasing application of TMS has promoted an increasing number of clinical studies. In this paper, a bibliometric analysis of existing studies was conducted to reveal current research hotspots and guide future research directions.Method: Relevant articles and reviews were obtained from the Science Citation Index Expanded of Web of Science Core Collection database. Data related to publications, countries, institutions, authors, journals, citations, and keywords in the studies included in the review were systematically analyzed using VOSviewer 1.6.18 and Citespace 6.2.4 software.A total of 1894 papers on the topic of TMS in PD between 1991 and 2022 were analyzed and visualized to identify research hotspots and trends in the field. The number of annual publications in this field of study has increased gradually over the past 30 years, with the number of annual publications peaking in 2022 (n=150). In terms of publications and total citations, countries, institutions, and authors from North America and Western Europe were found to make significant contributions to the field. The current hotspot focuses on the effectiveness of TMS for PD in different stimulation modes or different stimulated brain regions. The keyword analysis indicates that the latest research is oriented to the mechanism study of TMS for motor symptoms in PD, and the non-motor symptoms are also receiving more attention.Our study offers insights into the current hotspots and emerging trends of TMS in the rehabilitation of PD. These findings may serve as a guide for future research and the application of TMS for PD.